2022
DOI: 10.1177/00494755221110678
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic pulmonary aspergillosis and the antifungal drug resistance of Aspergillusspp. in pulmonary tuberculosis patients in Uzbekistan

Abstract: The aim of our study was to determine the prevalence of chronic pulmonary aspergillosis in pulmonary tuberculosis patients and the antifungal resistance of Aspergillus spp. isolates in Uzbekistan. Chronic pulmonary aspergillosis was detected in 11.4% and 20.0% of smear-positive and smear-negative pulmonary tuberculosis patients, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In Manaus, a cross-sectional study of 213 smear-negative ‘PTB’ patients found 15 with a pulmonary mycosis based on culture, serology, and CT scanning, of whom 10 (4.7%) had CPA ( Matsuda et al., 2021 ). In Uzbekistan, 12 (20%) of 60 smear-negative TB patients had CPA ( Toychiev et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Manaus, a cross-sectional study of 213 smear-negative ‘PTB’ patients found 15 with a pulmonary mycosis based on culture, serology, and CT scanning, of whom 10 (4.7%) had CPA ( Matsuda et al., 2021 ). In Uzbekistan, 12 (20%) of 60 smear-negative TB patients had CPA ( Toychiev et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, in Iran, nine of 94 (10%) of patients had CPA during or immediately after ATT therapy ( Hedayati et al., 2015 ). In Uzbekistan, 16 (11.4%) of 140 patients with smear-positive TB had CPA ( Toychiev et al., 2022 ). The lack of precise timing of CPA relative to initiation of ATT prevented the use of these studies in our estimates.…”
Section: Methodsmentioning
confidence: 99%
“…This study adds to the existing data on co-occurrence of pulmonary aspergillosis with active P.TB-both clinico-radiologically and microbiologically diagnosed. 8,9,[16][17][18][19][20] CPA) and still found the proportions comparable (7% at baseline and 14.6% at the end-of-TB-therapy of proven CPA) to that reported by Setianingrum et al (7.9% at baseline and 13.3% at the end-of-TBtherapy of combined proven and probable CPA). 8 However, the significance of diagnosis of such CPA in P.TB pa-…”
Section: Discussionmentioning
confidence: 65%
“…This study adds to the existing data on co-occurrence of pulmonary aspergillosis with active pulmonary tuberculosis – both clinico-radiologically and microbiologically diagnosed. 8, 15, 16, 17, 18, 19, 9 . Table 3 describes the available literature on the frequency of CPA at various time points in active P.TB patients.…”
Section: Discussionmentioning
confidence: 99%